Bacterial Ecology of Fermented Cucumber Rising pH Spoilage as Determined by Nonculture‐Based Methods. Issue 1 (25th November 2015) - Medina, Eduardo; Pérez‐Díaz, Ilenys M.; Breidt, Fred; Hayes, Janet; Franco, Wendy; Butz, Natasha; Azcarate‐Peril, María Andrea
Abstract: Fermented cucumber spoilage (FCS) characterized by rising pH and the appearance of manure‐ and cheese‐like aromas is a challenge of significant economical impact for the pickling industry. Previous culture‐based studies identified the yeasts Pichia manshurica and Issatchenkia occidentalis, 4 Gram‐positive bacteria, Lactobacillus buchneri, Lactobacillus parrafaraginis, Clostridium sp., and Propionibacterium and 1 Gram‐negative genus, Pectinatus, as relevant in various stages of FCS given their ability to metabolize lactic acid. It was the objective of this study to augment the current knowledge of FCS using culture‐independent methods to microbiologically characterize commercial spoilage samples. Ion Torrent data and 16S rRNA cloning library analyses of samples collected from commercial fermentation tanks confirmed the presence of L. rapi and L. buchneri and revealed the presence of additional species involved in the development of FCS such as Lactobacillus namurensis, Lactobacillus acetotolerans, Lactobacillus panis, Acetobacter peroxydans, Acetobacter aceti, and Acetobacter pasteurianus at pH below 3.4. The culture‐independent analyses also revealed the presence of species of Veillonella and Dialister in spoilage samples with pH above 4.0 and confirmed the presence of Pectinatus spp. during lactic acid degradation at the higher pH. Acetobacter spp. were successfully isolated from commercial samples collected from tanks subjected to air purging by plating on Mannitol Yeast Peptone agar. In contrast, Lactobacillus spp. were primarily identified in samples of FCS collected from tanks not subjected to air purging for more than 4 mo. Thus, it is speculated that oxygen availability may be a determining factor in the initiation of spoilage and the leading microbiota.